Using Top‐down and Bottom‐up Costing Approaches in LMICs: The Case for Using Both to Assess the Incremental Costs of New Technologies at Scale. (14th January 2016) - Cunnama, Lucy; Sinanovic, Edina; Ramma, Lebogang; Foster, Nicola; Berrie, Leigh; Stevens, Wendy; Molapo, Sebaka; Marokane, Puleng; McCarthy, Kerrigan; Churchyard, Gavin; Vassall, Anna
Abstract: Purpose: Estimating the incremental costs of scaling‐up novel technologies in low‐income and middle‐income countries is a methodologically challenging and substantial empirical undertaking, in the absence of routine cost data collection. We demonstrate a best practice pragmatic approach to estimate the incremental costs of new technologies in low‐income and middle‐income countries, using the example of costing the scale‐up of Xpert Mycobacterium tuberculosis (MTB)/resistance to riframpicin (RIF) in South Africa. Materials and methods: We estimate costs, by applying two distinct approaches of bottom‐up and top‐down costing, together with an assessment of processes and capacity. Results: The unit costs measured using the different methods of bottom‐up and top‐down costing, respectively, are $US16.9 and $US33.5 for Xpert MTB/RIF, and $US6.3 and $US8.5 for microscopy. The incremental cost of Xpert MTB/RIF is estimated to be between $US14.7 and $US17.7. While the average cost of Xpert MTB/RIF was higher than previous studies using standard methods, the incremental cost of Xpert MTB/RIF was found to be lower. Conclusion: Costs estimates are highly dependent on the method used, so an approach, which clearly identifies resource‐use data collected from a bottom‐up or top‐down perspective, together with capacity measurement, is recommended as a pragmatic approach to capture true incremental cost where routine cost data are scarce.